Carl Schmitt w polskich interpretacjach politologicznych 1984–2007 - Święcicki, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article discusses Polish political-science interpretations of the German legal and political theorist Carl Schmitt. It gives an overview of the main literature published between the 1980s and 2000s. Polish political scientists became interested in Schmitt only after a period of intensive studies conducted by lawyers. Polish political science, ideologically oriented during the times of the communist regime, took its leading role in Schmitt’s reception with the transformation of Poland’s political system. Interestingly, the flow of new translations of Schmitt’s writings in the first decades of the century shifted the reception substantially and moved it towards more philosophical and theological interpretations. The interpretations present in the field of political science have been divided into two kinds based on different methodologies: the first, focused on Schmitt as a political theorist, which aims at introducing his substantial contributions to political science, and the second, which focuses on Schmitt as a representative of conservatism. The article may serve as a practical introduction to Polish political-science research on Schmitt.
Keywords: Schmitt Carl; politologia; polska myśl polityczna; interpretacje